2010
DOI: 10.3109/09546630903410166
|View full text |Cite
|
Sign up to set email alerts
|

Sun protective behaviour in renal transplant recipients. A qualitative study based on individual interviews and the Health Belief Model

Abstract: This study shows that the Health Belief Model can be used to identify and describe factors that influence decisions and behaviour among RTRs regarding sun protective behaviour. We recommend that RTRs are informed about the potential severity of skin cancer, and about the importance of consistent sun protective behaviour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 16 publications
0
25
0
Order By: Relevance
“…Similarly to previous findings in other outdoor professions, the decision not to engage in primary prevention can at least partly be attributed to a lack of knowledge about KC and UVR. For example, an Australian qualitative study assessing parents’ knowledge, attitudes and beliefs regarding sun protection in their children found that detailed knowledge of the risks of sun exposure outweighed all other influencing factors, whereas renal transplant recipients ‘did not perceive the threat of skin cancer as an important health problem’, even though they were aware of their increased risk of KC . Therefore, beyond basic strategies to improve knowledge, strategies to increase self‐efficacy could be the key to preventing KC in farmers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly to previous findings in other outdoor professions, the decision not to engage in primary prevention can at least partly be attributed to a lack of knowledge about KC and UVR. For example, an Australian qualitative study assessing parents’ knowledge, attitudes and beliefs regarding sun protection in their children found that detailed knowledge of the risks of sun exposure outweighed all other influencing factors, whereas renal transplant recipients ‘did not perceive the threat of skin cancer as an important health problem’, even though they were aware of their increased risk of KC . Therefore, beyond basic strategies to improve knowledge, strategies to increase self‐efficacy could be the key to preventing KC in farmers.…”
Section: Discussionmentioning
confidence: 99%
“…For example, an Australian qualitative study assessing parents' knowledge, attitudes and beliefs regarding sun protection in their children found that detailed knowledge of the risks of sun exposure outweighed all other influencing factors, 31 whereas renal transplant recipients 'did not perceive the threat of skin cancer as an important health problem', even though they were aware of their increased risk of KC. 33 Therefore, beyond basic strategies to improve knowledge, strategies to increase self-efficacy could be the key to preventing KC in farmers. Even when avoiding sun exposure is not possible, for example when making hay, other solutions can be found to reduce individual UVR exposure.…”
Section: Discussionmentioning
confidence: 99%
“…However, the benefits of adequate VitD status may be less generally appreciated . In addition, patients who have previously suffered from skin cancer are actively encouraged to avoid direct sunlight and to rigorously use sun protective measures which may impact on their VitD levels, although compliance with this advice may be variable .…”
mentioning
confidence: 99%
“…The diffuse form of disease will usually have anti-topoisomerase I (Scl-70), and anti-RNP antibodies, while patients with the limited form are more likely to have anti-centromere positive titers. Identifi cation of these antibodies can help in determination of prognosis, as it may help distinguish patient that remain as a limited type or progress to the diffuse form [ 86 ]. Additionally prevalence of anti-RNP in systemic sclerosis may indicate an increased risk of associated malignancy [ 87 ].…”
Section: Workup Laboratory Findings Imaging Studiesmentioning
confidence: 99%